Community Development Through Activities Teaching Religious Education to Children at SDN 2 Arahan Lor - Tiya Lestari (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The main objective of KKN is to enable students to directly apply the knowledge they have acquired in the field of education to the community. KKN also serves as a means for students to gain broader insights into knowledge and experiences within society. From the observations made, issues have been identified among adolescents and the community in Desa Arahan Lor, namely the scarcity of highly educated individuals and the lack of religious knowledge. Additionally, the lack of education has resulted in a deficiency in understanding and practicing religious activities. To address these issues, a program titled